Merekah Harap Produk UMKM Melalui Media Sosial dan E-Commerce di Desa Terantang Kabupaten Barito Kuala - Setiawan, Fahrul Ruzi; Zulaikha, Siti; Ungawaru, Shinta Ardini Prasasti; Putra, Aditya Dimas Anggi; Sari, Ayu Permata; Vinanda, Astri Dea Ranindiaz; Putri, Azmi Anugerah; Irmayani, Irmayani (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
One of the sectors affected by technological developments is the micro, small and medium enterprise (MSME) sector, especially in the marketing process. Social media can be utilized by MSME actors as a promotional medium. However, in the midst of technological advances, there are limitations on the UMKM players of kelakai chips in Terantang Village, Mandastana District, Barito Kuala Regency, especially related to how to brand and promote products through social media. The solution encouraged by the service team is a socialization program on the potential and marketing of kelakai chips through e-commerce and social media. The aim is to invite the community to strengthen MSMEs through online marketing so that they can reach more enthusiasts (consumers). The program is implemented through activities: 1) Socialization; 2) Marketing class; and, 3) Product photography class. The targets of the program are kelakai chips MSME players and the Terantang Village community, especially mothers. This program was able to strengthen the spirit and entrepreneurial spirit of the kelakai chips MSME players and the Terantang Village community. The benefits of this program are that the kelakai chips MSME players have an unlimited mindset and the ability to promote their processed products, so as to increase the income and welfare of their families and surrounding communities. The achievements of this program will have implications for the ability of MSMEs in Terantang Village to survive in running their businesses. After the implementation of the program, the service team gained various knowledge on how to help market community products that have limited technological knowledge.